Biocomposites based on chemically modified cellulose fibers with renewable fatty‐acid‐based thermoplastic systems: Effect of different fiber treatments. Issue 35 (19th May 2016) - Reulier, M.; Perrin, R.; Avérous, L.
ABSTRACT: Advanced biocomposites, based on binary and ternary systems, were developed with thermoplastic matrices such as thermoplastic polyurethane (TPU) and polyamide (DAPA) obtained from dimers of fatty acids, and cellulose fibers (CF). The CF were modified to display high interfacial adhesion and compatibility with the rather hydrophobic matrices. Different routes were considered such as grafting onto with prepolymers, or grafting from with aromatic isocyanate or fatty acid. An original approach of this work is to consider CF as a polyol with an equivalent hydroxyl index obtained by titration. In order to understand better the effect of each phase, the resulting modified CF were tested with neat TPU and DAPA matrices. The most promising fibers treatments were then tested with 80/20 and 50/50 wt %/wt % TPU/DAPA blends. Properties at the molecular and macromolecular scale were investigated. Improvement of the interfacial adhesion between the fibers and the polymers were observed. From the different grafting approaches tested, the best performing were the isocyanate‐terminated prepolymer and the silane‐terminated prepolymer modifications. In comparison with neat CF, modification with isocyanate‐terminated prepolymer improved threefold the storage and Young's modulus of TPU biocomposites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43878. Abstract :